PENDIDIKAN KESEHATAN DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN ANEMIA IBU HAMIL - Misroh Mulianingsih; Henny Yolanda; Sopian Khalid; Hayana (Jurnal LENTERA, 2021)
Maternal mortality in pregnant women 17.52% occurred during pregnancy. One of the illnesses in pregnant women is anemia which can cause maternal death due to bleeding during delivery. Knowledge of pregnant women about anemia and nutrients rich in iron and folic acid during pregnancy are needed to ensure a good pregnancy and influence hemoglobin levels. The purpose of this community service is to increase the knowledge of pregnant women about anemia so that they can change their behavior in preventing and overcoming anemia. The method used is the lecture method and using flipcharts aimed at pregnant women at the Gerung Utara Polindes, Pohdana Village. The counseling that is carried out is an activity or effort to convey information about anemia to pregnant women, including the definition, causes, risk factors, signs and symptoms, impacts, and handling/prevention of anemia in pregnant women. To monitor the increase in knowledge of pregnant women, used pre and post-test. The results show a significant increase in participants' insight and understanding. There was an increase in the average knowledge of pregnant women about anemia from 5.93 to 7.80. Suggestions for health centers and health observers, especially pregnant women, are to provide more information about the health of pregnant women with various media so that pregnant women get the correct information and indirectly prevent risks to mothers and babies. Keyword; Health education, anemia of pregnant women